Carbon fiber-reinforced epoxy with 100% fiber recycling by transesterification reactions - Wu, Jianqiao; Pan, Ying; Ruan, Ziyi; Zhao, Ziji; Ai, Jing; Ban, Jinghai; Jing, Xianghai (Frontiers in Materials, 2022)
Carbon fiber reinforced epoxy is the most commonly used advanced composite with high performance. However, these composites usually face to the intractable disposal problems in their lifecycles, due to the stable cross-linked network structures of epoxy. To address this dilemma, this work proposed a facile yet efficient strategy for recycling carbon fibers from traditional carbon fiber reinforced epoxy composites using epoxy-anhydride systems as matrix. The diglycidyl ester of aliphatic cyclo (DGEAC) and methylhexahydrophthalic anhydride (MHHPA) were used as matrix, while T300 carbon fiber woven was used as reinforcement, to construct composites CF/DGEAC/MHHPA. The epoxy matrix exhibited high glass transition temperature (Tg = 126oC), high decomposition temperature (Td5 = 300oC) and good solvent resistance. By using 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as catalyst, the DGEAC/MHHPA networks could be degraded completely in ethylene glycol (EG) at 180oC within 6 h, because of the transesterification reactions (TERs) between EG and networks. Taking advantages of this result, a process of fiber recycling was developed for carbon fiber composites, where the cross-linked networks of epoxy could be degraded with carbon fiber 100% recycling. Furthermore, the recycled carbon fiber maintained nearly 100% similarity of surface microscopic morphology and chemical structure compared with virgin ones. This work proposed a simple and efficient strategy for recycling carbon fiber from traditional high-performance composites, which offered a convenient concept for the cyclic utilization of advanced composites.